PENERAPAN AROMATERAPI LAVENDER TERHADAP PENURUNAN NYERI PADA PASIEN POST SECTIO CAESAREA DI RUANG CILAMAYA BARU RSUD KARAWANG - Dina Hartini; Serly, Serly; Gustiara, Gustiara (Bajang Institute, 2025)
A Caesarean section (CS) is a surgical procedure to deliver a baby through an incision in the abdominal wall and uterus, which often causes postoperative pain. Pain that is not managed properly can disrupt comfort and slow the mother's recovery process. Lavender aromatherapy is a non-pharmacological therapy that can be used to reduce pain through its natural relaxing and analgesic effects. This study aims to determine the application of lavender aromatherapy to reduce pain in post-cesarean section patients in the Cilamaya Baru Ward, Karawang Regional Hospital. Twenty participants, consisting of nurses, participated in the activity. Evaluation was carried out using a pre-test and post-test to assess knowledge improvement, as well as observation of skills during simulation practice. The results of the activity showed an increase in participant knowledge from an average of 58% (pre-test) to 89% (post-test). In addition, 90% of participants were able to administer the therapy correctly. Participants also showed high enthusiasm in participating in the entire series of activities. Socialization of the application of lavender aromatherapy to reduce signs and symptoms of pain in post-op section patients has proven effective in increasing nurses' knowledge and skills and reducing signs and symptoms of low self-esteem. Lavender aromatherapy was proven effective in reducing pain in post-cesarean section patients and can be applied as a safe, easy, and economical non-pharmacological nursing intervention to improve patient comfort during recovery